Relevansi Standar Kopetensi Lulusan Sikap Madrasah Aliyah Dengan Obat Penyakit Hati Pemikiran Ibnu Qayyim Al-Jauziah - Bainar Bainar; Taufik Helmi (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2021)
Competency standards for graduates of Madrasah Aliyah graduates are criteria regarding the level of ability regarding the attitudes that students must achieve after completing their studies at Madrasah Aliyah, namely having behavior that reflects the divinity of a believer and has noble character towards others and the universe environment, thus this attitude standard aims to produce graduates who have healthy hearts (qolbun salim) so that their lives are happy in this world and the hereafter. Humans are born into this world in a state of not knowing anything, in order to know something, Allah gave humans the potential in the form of hearing, sight and heart so that they can be educated to become human beings who have qolbun salim obedient to Allah and His messenger. But that hope is difficult to achieve because humans have been plagued with liver disease that needs to be treated. This after research is relevant to the opinion of Ibn Qayyim Al-Jauziah about liver disease drugs.